PREVALENCE OF PSYCHOLOGICAL SYMPTOMS IN STUDENTS OF THE FACULTY OF HEALTH STUDIES UNIVERSITY OF MOSTAR (Zdravstveni glasnik, 2024)
Introduction: The student population is in a period of psychological maturation during which a personsearches for their identity and gradually accepts the role and responsibilities of an adult. Studentship isconsidered a very sensitive period, because up to the age of 24 years has the highest prevalence of mentaldisorders appearing for the first time.Objective: Investigate the prevalence of psychological symptoms in students of the Faculty of HealthStudies of the University of Mostar.Subjects and methods: The study group consisted of students of the Faculty of Health Studies of theUniversity of Mostar (N=100), and the control group consisted of students of the Faculty of Kinesiology ofthe University of Mostar (N=100). The data were collected using a socio-demographic questionnairedesigned specifically for this research and The Symptom Checklist-90-R (SCL-90-R).Results: Students who used psychoactive substances were statistically significantly more likely to drinkalcoholic beverages and smoke tobacco when compared to the group of students who do not usepsychoactive substances. Students of the Faculty of Health Studies achieved statistically significantly higherscores on the scales for psychological symptoms (SCL-90-R): obsessive-compulsive symptoms,interpersonal sensitivity, depression, anxiety, paranoia, psychotic features and non-specific psychologicalsymptoms when compared to kinesiology students.Conclusion: Students of the Faculty of Health Studies of the University of Mostar have a statisticallysignificantly higher prevalence of psychological symptoms when compared to students of the Faculty ofKinesiology.